The role of governance in the effect of the internet on financial inclusion in sub-Saharan Africa - Armand F. Akpa; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
Financial inclusion is a necessary condition for the population to get access to credit. Despite the efforts made by governments and policy makers, the rate of financial inclusion in Sub-Saharan African (SSA) countries remains low. The internet can be one of the options to increase the rate of financial inclusion in SSA. But the use of internet in SSA remains low due to the poor quality of the internet and to its high cost. So, good governance quality can consolidate internet infrastructure in order to promote the internet. This paper analyses the role of governance quality in the relationship between internet and financial inclusion in SubSaharan African countries. The study utilises data from the International Monetary Fund (IMF) database for indicators of financial inclusion, World Development Indicators (WDI) for internet users and World Governance Indicators (WGI) for governance indicators over the period 2004 to 2020. Analysing the data using the System Generalized Method of Moments (SGMM), the results show that the internet can be effectively complemented with the quality of governance to improve financial inclusion.Thresholds of governance that are needed for the internet to promote financial inclusion are provided. The established thresholds are as follows: (i) 0.300 'voice and accountability' and 'government effectiveness', respectively; (ii) 0.250 'rule and law'; (iii) 2.500 'economic governance' and (iv) 1.000 'institutional governace' and 'general governance', respectively. Policies aimed at reinforcing the quality of governance in SSA countries could help consolidate internet infrastructure to promote internet usage and in turn improve financial inclusion.
Keywords: O30; G20; H11; 330; Internet; financial inclusion; governance quality